A Critical Assessment of the Equal-Environment Assumption of the Twin Method for Schizophrenia - Fosse, Roar; Joseph, Jay; Richardson, Ken (Frontiers in Psychiatry, 2015)
The classical twin method (CTM) is central to the view that schizophrenia is ~80% heritable. The CTM rests on the equal environments assumption (EEA) that identical and fraternal twin pairs experience equivalent trait relevant environmental exposures. The EEA has not been directly tested for schizophrenia with measures of child social adversity, which is particularly etiologically relevant to the disorder. However, if child social adversity is more similar in identical than fraternal pairs in the general twin population, the EEA is unlikely to be valid for schizophrenia, a question which we tested in this study. Using results from prior twin studies, we tested if intraclass correlations for the following five categories of child social adversity are larger in identical than fraternal twins: bullying, sexual abuse, physical maltreatment, emotional neglect and abuse, and general trauma. Eleven relevant studies that encompassed 9119 twin pairs provided 24 comparisons of intraclass correlations, which we grouped into the five social exposure categories. Fisher’s z-test revealed significantly higher correlations in identical than fraternal pairs for each exposure category (z ≥ 3.53, p <.001). The difference remained consistent across gender, study site (country), sample size, whether psychometric instruments were used, whether interviewing was proximate or distant to the exposures, and whether informants were twins or third persons. Combined with other evidence that the differential intraclass correlation for child social adversity cannot be explained by evocative gene-environment covariation, our results indicate that the CTM does not provide any valid indication of genomic effects in schizophrenia.